2016
DOI: 10.1080/19490976.2016.1182293
|View full text |Cite
|
Sign up to set email alerts
|

A humanized microbiota mouse model of ovalbumin-induced lung inflammation

Abstract: There is increasing evidence for a role of early life gut microbiota in later development of asthma in children. In our recent study, children with reduced abundance of the bacterial genera Lachnospira, Veillonella, Faecalibacterium, and Rothia had an increased risk of development of asthma and addition of these bacteria in a humanized mouse model reduced airway inflammation. In this Addendum, we provide additional data on the use of a humanized gut microbiota mouse model to study the development of asthma in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 24 publications
(25 reference statements)
3
26
0
Order By: Relevance
“…The individual opposing shift in the abundance of Lachnospira and Clostridium neonatale in the first three months of life suggests that these specific gut bacteria play a role in protecting or promoting development of a preschool age asthmatic phenotype, in addition to the previously identified roles in other atopic disorders. This bacterial dysbiosis was confirmed in other studies of the same group of authors, in which they showed the relative abundance of the bacterial genera Lachnospira and the decrease of Veillonella , Faecalibacterium , and Rothia in children at risk of asthma [53]. This reduction was accompanied by decreased levels of faecal acetate and dysregulation of enterohepatic metabolites.…”
Section: Microbiome and Asthmasupporting
confidence: 77%
“…The individual opposing shift in the abundance of Lachnospira and Clostridium neonatale in the first three months of life suggests that these specific gut bacteria play a role in protecting or promoting development of a preschool age asthmatic phenotype, in addition to the previously identified roles in other atopic disorders. This bacterial dysbiosis was confirmed in other studies of the same group of authors, in which they showed the relative abundance of the bacterial genera Lachnospira and the decrease of Veillonella , Faecalibacterium , and Rothia in children at risk of asthma [53]. This reduction was accompanied by decreased levels of faecal acetate and dysregulation of enterohepatic metabolites.…”
Section: Microbiome and Asthmasupporting
confidence: 77%
“…This microbial profile was associated with increased production of the pro‐inflammatory metabolite 12,13 DiHOME. In a different cohort of children ages 6–17, there was no association between gut microbiota and asthma . Adults with long‐term asthma were found to have a decreased abundance of Bifidobacteria spp .…”
Section: Microbiota and Asthma (Human Evidence)mentioning
confidence: 93%
“…Nevertheless, the causal role of dysfunctional gut microbiota in driving IBD flares of individual patients is poorly understood and requires the implementation of translational models 19 . Transplantation of fecal microbiota from patients into germ-free recipient mice has been used to recapitulate a variety of disease phenotypes, including IBD, and therefore provides a clinically relevant tool to mechanistically address microbe-host interactions [20][21][22][23] . In this study, we took advantage of autologous hematopoietic stem cell transplantation (HSCT), a therapeutic intervention that has significant and prolonged effects on a subset of severe and highly refractory CD patients, bringing them into drug-free remission, with a proportion of these patients relapsing over time.…”
mentioning
confidence: 99%